The mining industry and the developing countries - Bosson, Rex.; Varon, Bension (New York : Published for the World Bank [by] Oxford University Press, 1977)
This book is designed to provide an overview of the world mining industry- its structure, objectives and operation.
Includes index.
Includes bibliographical references: p. 275-283.
II 18/01/2019
Loans
Keywords: Mineral industries